Energy emissions, consumption and impact of urban households: A review. (September 2021) - Verma, Pramit; Kumari, Tanu; Raghubanshi, Akhilesh Singh
Abstract: About 3 billion people still rely on traditional sources of fuel. Biomass-based fuels were responsible for more than 4 million deaths in 2012. Household energy consumption is steadily increasing across cities due to the urbanization of rural areas, more economic and travel activities. In this review, Multiple Correspondence Analysis (MCA) and other bibliometric tools were applied to determine the conceptual structure and typological thematic areas of household emissions in urban areas. The current state of knowledge and opportunities towards creating carbon-neutral cities indicated that while most of the research was focussed on cities and regions of developed countries and China, the mitigation activities grouped under three broad heads - reducing emissions, consumption and impact of household emissions. Strong heterogeneity between the urban and rural areas, fuel options and human choices gave rise to fuel-stacking in developing countries. Integrated modelling and inclusion of environmental and human behavioural components into economic models were recognised as emerging fields oriented towards a systems approach. Accessibility and availability of clean energy and clean energy appliances were identified as the biggest challenges. To create carbon-neutral urban areas, integrated modelling should include categorization of carbon policy according to local conditions, analysis of feedback loops, embedded emissions, the global and regional impact of household consumption patterns, and uncertainty associated with mitigation measures. Graphical abstract: Image 1 Highlights: Carbon neutral cities should have access equality despite income inequality. Multiple Correspondence Analysis indicated mitigation research focused on emissions, consumption and impacts. Integrated modelling and general equilibrium models were the two emerging themes. Risk, uncertainty, embedded emissions and feedback loops should be integrated into emission models. Availability and accessibility to cleaner fuels is the biggest challenge for creating carbon-neutral cities.